First records of Phyllostomus hastatus (Pallas, 1767) (Chiroptera, Phyllostomidae), Greater Spear-nosed Bat, in Mexico - J. Manuel Aranda-Coello; L. Arturo Hernández-Mijangos; Manuel Weber (Check List, 2025)
We report Phyllostomus hastatus (Pallas, 1767), Greater Spear-nosed Bat, for the first time in Mexico. We captured two adult males in the Lacandona rainforest, in Chiapas, Mexico. These records extend the known northern distribution limit of the species by 120 km from the nearest occurrence in Lanquín, Alta Verapaz, Guatemala. Given the limited distribution of P. hastatus in the country and its potential vulnerability due to habitat loss, we highlight the need for more studies and conservation actions, aiming to its inclusion in the national list of threatened species.